Comparison of Bilateral vs. Staged Unilateral Deep Brain Stimulation (DBS) in Parkinson's Disease in Patients Under 70 Years of Age. Issue 1 (16th November 2015) - Petraglia, Frank W.; Farber, S. Harrison; Han, Jing L.; Verla, Terence; Gallis, John; Lokhnygina, Yuliya; Parente, Beth; Hickey, Patrick; Turner, Dennis A.; Lad, Shivanand P.
Abstract : Objective: The most popular surgical method for deep brain stimulation (DBS) in Parkinson's disease (PD) is simultaneous bilateral DBS. However, some centers conduct a staged unilateral approach advocating that reduced continuous intraoperative time reduces postoperative complications, thus justifying the cost of a second operative session. To test these assumptions, we performed a retrospective analysis of the Truven Health MarketScan® Database. Methods: Using the MarketScan Database, we retrospectively analyzed patients that underwent simultaneous bilateral or staged unilateral DBS between 2000 and 2009. The main outcome measures were 90‐day postoperative complication rates, number of reprogramming hours one year following procedure, and annualized healthcare cost. The outcome measures were compared between cohorts using multivariate regressions controlling for appropriate covariates. Results: A total of 713 patients that underwent DBS between 2000 and 2009 met inclusion criteria for the study. Of these patients, 556 underwent simultaneous bilateral DBS and 157 received staged unilateral DBS. No statistically significant differences were found between groups in the rate of infection (simultaneous: 4.3% vs. staged: 7.0%; p = 0.178), pneumonia (3.1% vs. 5.7%; p = 0.283), hemorrhage (2.9% vs. 2.5%; p = 0.844), pulmonary embolism (0.5% vs. 1.3%), and device‐related complications (0.5% vs. 0.0%). Patients in the staged cohort had a higher rate of lead revision in 90 days (3.2% vs. 12.7%; RR = 3.07; p < 0.001). The staged cohort had a higher mean (SD) number of reprogramming hours within one year of procedure (6.0 ± 5.7 vs. 7.8 ± 8.1; RR = 1.17; p < 0.001). No significant difference was found between the mean (SD) annualized payments between the cohorts ($86, 100 ± $94, 700 vs. $102, 100 ± $121, 500; p = 0.148). Conclusion: Our study did not find a significant difference between 90‐day postoperative complication rates or annualized cost between the staged and simultaneous cohorts. Thus, we believe that it is important to consider other factors when deciding between the staged and simultaneous DBS. Such factors include patient convenience and the laterality of symptoms.